Implementation of E-Filling and Taxpayer Awareness of Taxpayer Compliance with Tax Socialization as a Moderator - Wahyuni, Risca Nur; Umaimah, Umaimah (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p08, 2025)
This study aims to analyze the effect of E-Filling implementation and taxpayer awareness on taxpayer compliance, with tax socialization as a moderating variable. The study examines taxpayer compliance at KPP Pratama Gresik with a research population of individual taxpayers in Gresik who are registered at KPP Pratama Gresik totaling 275,042 taxpayers. Sampling using purposive sampling technique as many as 80 respondents with primary data sources obtained through questionnaires distributed according to sample criteria. Data analysis using Structural Equation Modeling (SEM-PLS) to assess the relationship between variables. The results of the analysis show that the application of E-Filling and Taxpayer Awareness has a positive effect on Taxpayer Compliance, but Tax Socialization does not moderate the relationship between the two variables on Taxpayer Compliance. Keywords: E-Filling; Compliance; Awareness; Taxation; Socialization